2019
DOI: 10.1136/thoraxjnl-2018-212812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiovascular risk in a lung cancer screening cohort

Abstract: IntroductionLung cancer screening (LCS) by low-dose computed tomography (LDCT) offers an opportunity to impact both lung cancer and coronary heart disease mortality through detection of coronary artery calcification (CAC). Here, we explore the value of CAC and cardiovascular disease (CVD) risk assessment in LCS participants in the Lung Screen Uptake Trial (LSUT).MethodsIn this cross-sectional study, current and ex-smokers aged 60–75 were invited to a ‘lung health check’. Data collection included a CVD risk ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Other incidental finding outcomes have been reported elsewhere. 11 12 Study participants with complete smoking and lung cancer risk data were included. Descriptive statistics were used to present the data pertaining to pulmonary nodules and lung cancer outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Other incidental finding outcomes have been reported elsewhere. 11 12 Study participants with complete smoking and lung cancer risk data were included. Descriptive statistics were used to present the data pertaining to pulmonary nodules and lung cancer outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Coronary artery calcification is commonly detected in lung cancer screened participants and increasing severity of disease is associated with increasing risk of cardiovascular events and allcause mortality. [151][152][153][154][155] A screening LDCT can also identify the presence of emphysema as well as vertebral fractures and osteoporosis which are independently associated with increased all-cause mortality. 156,157 LDCT chest scans, utilized for lung cancer screening, can therefore be used to evaluate the presence of other undiagnosed comorbidities that are predictive of increased all-cause mortality, providing a potential opportunity to further improve health outcomes.…”
Section: Other Tobacco-related Comorbiditiesmentioning
confidence: 99%
“…To evaluate its true value, outcome studies comparing correlation between visually graded CAC and QRISK2 score with cardiovascular end-points should be performed. While previous studies have shown that only a small number of participants from LCS cohorts will have 2012 individuals were invited for LDCT 770 participants underwent LDCT 680 individuals were included in the analysis 235 participants were excluded due to ineligibility 85 participants were excluded due to history of CVD 5 participants were excluded due to missing QRISK2 score data 1005 individuals responded and were screened for eligibility Figure 1 Flow diagram of the stages and participants who were recruited in the study of Ruparel et al [7]. Reproduced and modified from [7] with permission.…”
Section: Commentarymentioning
confidence: 99%
“…77% in the 10-20% and 50% in the >20% groups reported no use of statins despite being in the CVD risk cohort. Data from [7]. a CVD event, most look at only fatal CHD events, so in future studies, non-fatal coronary events should be studied.…”
Section: Commentarymentioning
confidence: 99%